Analisis Penerapan Rumah Sakit Ramah Lingkungan (Green Hospital) pada Dua Rumah Sakit di Indonesia - Safiera Amelia; Jaslis Ilyas (Syntax Corporation, 2023)
The increase in the amount of daily waste generated by hospitals has contributed to climate change and global warming in the world. This is the basis for the development of the green hospital concept as an effort to reduce the impact of environmental damage in the health sector. Green hospital assessment in Indonesia can refer to the assessment tool developed by the Green Building Council Indonesia (GBCI) called greenship version 1.1. This study aims to analyze the differences in the implementation of green hospitals according to GBCI guidelines in two hospitals as a reference for hospitals in Indonesia. This research method is a narrative review, by searching grey literature according to the inclusion criteria. Based on the literature selection, data from two theses were obtained at Embung Fatimah Hospital Batam in 2017 and PON Prof. Dr. Mahar Mardjono Hospital in 2021 which will be analyzed for the three categories that have the highest proportion of benchmark values. The results show that the implementation of the Energy Efficiency and Conservation category at RS PON Prof. Dr. dr. Mahar Mardjono (62.5%) is better than at RSUD Embung Fatimah Batam (31.3%), the implementation of the Water Conservation category at RSUD Embung Fatimah Batam (50%) is better than at RS PON Prof. Dr. dr. Mahar Mardjono in 2021. Dr. dr. Mahar Mardjono (35%) and the implementation of the Indoor Health and Comfort category at RS PON Prof. Dr. dr. Mahar Mardjono (30.8%) and RSUD Embung Fatimah Batam (23.1%) still requires more attention because the percentage of achievements is still below 50%.